2019
DOI: 10.2147/clep.s214909
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validity of ICD-10 diagnoses of overweight and obesity in Danish hospitals</p>

Abstract: PurposeHealth care databases may be a valuable source for epidemiological research in obesity, if diagnoses are valid. We examined the validity and completeness of International Classification of Diseases, 10th revision [ICD-10] diagnosis coding for overweight/obesity in Danish hospitals.Patients and methodsWe linked data from the Danish National Patient Registry on patients with a hospital diagnosis code of overweight/obesity (ICD-10 code E66) with computerized height and weight measurements made during hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…This is also a likely explanation for the relatively low prevalence of overweight or obesity in this study. The positive predictive value of these diagnoses in the registries is, however, high [28].…”
Section: Plos Medicinementioning
confidence: 94%
“…This is also a likely explanation for the relatively low prevalence of overweight or obesity in this study. The positive predictive value of these diagnoses in the registries is, however, high [28].…”
Section: Plos Medicinementioning
confidence: 94%
“…We had no information on the exact BMIs. Although we found that the overweight and obesity diagnosis code had high specificity, completeness of coding of overweight and obesity was low . Obesity is rarely a primary cause of hospital admission, and it may be an important contributing factor to many admissions.…”
Section: Discussionmentioning
confidence: 59%
“…Obesity is rarely a primary cause of hospital admission, and it may be an important contributing factor to many admissions. Completeness was higher among women than men, and was highest among patients aged 30–39 years, which must be taken into account when interpreting our results . We did not have access to individual patient records, thus we had no information on smoking, alcohol intake, and physical activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The researchers found discrepancies at all levels and variability among the different variables, with some showing high accuracy and others showing low quality. Gribsholt et al, [6] also looked at multiple information sources to validate the diagnoses of overweight and obesity in Denmark. The researchers compared diagnoses of overweight and obesity with BMI data.…”
Section: Quality Of Ehr Datamentioning
confidence: 99%